Selected environmental impacts of forest harvesting operations with varying degree of mechanization - Labelle, Eric R. (Array, 2019)
Climate change affects forest ecosystems, impacting timber production and eco-services. Conversely, sustainable forest management has been identified as a means to help mitigate carbon dioxide emissions, a greenhouse gas and contributor to climate change, while also maximizing multiuse benefits through close-to-nature silviculture. In this study, a life cycle assessment was performed on forest harvesting operations at three research sites to provide real-world understanding of the selected environmental impacts associated with harvesting systems typical of Germany: motor-manual (chainsaw and forest tractor), semi-mechanized (single-grip harvester, chainsaw, and forwarder), and fully-mechanized (single-grip harvester and forwarder). Environmental impact categories assessed included greenhouse gas emissions, particulate matter emissions, and non-renewable energy consumption. Results from the three research sites were estimated on a machine basis. The semi-mechanized system resulted in the lowest environmental impact, the majority of which was attributed to felling and processing operations. Next, the environmental impacts were estimated for a complete rotation period and compared amongst the different harvesting systems. According to results, semi-mechanized harvesting systems had the lowest impact over the full rotation period as well as for thinning treatments when compared to motor-manual and fully-mechanized systems. The fully-mechanized system performed the best for final felling treatments. Considering variability between the research sites as well as the system boundary assessed, a diversified approach to harvesting operations may be considered, integrating semi-mechanized and fully-mechanized systems for different treatments throughout the rotation period.